Effective contract in higher school: the implementationpractice - Sergey N. Postnikov; Alena V. Andrienko (Высшее образование в России)
The article describes in detail the implementation practice of effective contract for faculty members of the university, from planning to the results of the effectiveness. The authors consider the structure of indices matrix for evaluation the efficiency of faculty staff activities. The categories of faculty positions are introduced, and an assessment scale is presented.